2014
DOI: 10.1186/1472-6882-14-142
|View full text |Cite
|
Sign up to set email alerts
|

Memory-enhancing activities of the aqueous extract of Albizia adianthifolia leaves in the 6-hydroxydopamine-lesion rodent model of Parkinson’s disease

Abstract: BackgroundAlbizia adianthifolia (Schumach.) W. Wright (Fabaceae) is a traditional herb largely used in the African traditional medicine as analgesic, purgative, anti-inflammatory, antioxidant, antimicrobial and memory-enhancer drug. This study was undertaken in order to evaluate the possible cognitive-enhancing and antioxidative effects of the aqueous extract of A. adianthifolia leaves in the 6-hydroxydopamine-lesion rodent model of Parkinson’s disease.MethodsThe effect of the aqueous extract of A. adianthifol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 42 publications
2
39
0
Order By: Relevance
“…Aurantiamide acetate and various extracts of Albizia species have been reported to possess strong antioxidant activity with these plant extracts reported to be good sources of natural antioxidants able to prevent the progression of various oxidative stresses (Beppe et al, 2014;Kokila et al, 2013) associated with some CNS disorders. Beppe et al (2014) reported that the aqueous leaf extract of A. adianthifolia possess memoryenhancing effects linked with antioxidant activities in the 6-OHDA (6-hydroxydopamine)-lesion rodent model of Parkinson's disease.…”
Section: Discussionmentioning
confidence: 97%
“…Aurantiamide acetate and various extracts of Albizia species have been reported to possess strong antioxidant activity with these plant extracts reported to be good sources of natural antioxidants able to prevent the progression of various oxidative stresses (Beppe et al, 2014;Kokila et al, 2013) associated with some CNS disorders. Beppe et al (2014) reported that the aqueous leaf extract of A. adianthifolia possess memoryenhancing effects linked with antioxidant activities in the 6-OHDA (6-hydroxydopamine)-lesion rodent model of Parkinson's disease.…”
Section: Discussionmentioning
confidence: 97%
“…Pérez-Barrón et al [122] explored the antioxidant and neuroprotective effect of Buddleja cordata methanolic extract in the 1-methyl-4-phenylpyridinium induced PD rat model. Beppe et al [123] suggested that the aqueous extract of Albizia adianthifolia leaves possesses antioxidant potential, which was responsible for the memory-enhancing activities in the rodent model of PD.…”
Section: Natural Products and Parkinson's Diseasementioning
confidence: 99%
“…Beppe et al, 2014 showed that when rats with neurotoxicity induced by 6-hydroxy dopamine injection treated withaqueous extract obtained from Albizia adianthifolia significantly leads to increase of spontaneous alternations percentage, reduction of working memory errors and reference memory errors. Indeed, it had good effect to improve spatial memory 35 .…”
Section: Effects Of Extracts Isolated From Herbs In Treatment Of Parkmentioning
confidence: 98%